Immunomodulation and protection induced by DNA-hsp65 vaccination in an animal model of arthritis - Santos-Junior, R. R.; Sartori, A.; De Franco, M.; Filho, OGR; Coelho-Castelo, AAM; Bonato, VLD; Cabrera, WHK; Ibanez, O. M.; Silva, C. L. (Mary Ann Liebert, Inc., 2005)
We described a prophylactic and therapeutic effect of a DNA vaccine encoding the Mycobacterium leprae 65- kDa heat shock protein (DNA-hsp65) in experimental murine tuberculosis. However, high homology of the vaccine to the corresponding mammalian hsp60, together with the CpG motifs in the plasmidial vector, could trigger or exacerbate an autoimmune disease. In the present study, we evaluate the potential of DNA- hsp65 vaccination to induce or modulate arthritis in mice genetically selected for acute inflammatory reaction (AIR), either maximal (AIRmax) or minimal (AIRmin). Mice immunized with DNA-hsp65 or injected with the corresponding DNA vector (DNAv) developed no arthritis, whereas pristane injection resulted in arthritis in 62% of AIRmax mice and 7.3% of AIRmin mice. Administered after pristane, DNA- hsp65 downregulated arthritis induction in AIRmax animals. Levels of interleukin (IL)- 12 were significantly lower in mice receiving pristane plus DNA- hsp65 or DNAv than in mice receiving pristane alone. However, when mice previously injected with pristane were inoculated with DNA- hsp65 or DNAv, the protective effect was significantly correlated with lower IL-6 and IL-12 levels and higher IL-10 levels. Our results strongly suggest that DNA-hsp65 has no arthritogenic potential and is actually protective against experimentally induced arthritis in mice.